Isolation and localization of cells expressing Sca-1 in the Adult Mouse Ovary: An evidence for presence of Mesenchymal Stem cells - Majidi Zolbin, Masoumeh; Mokhtari, Tahmineh; Amidi, Fardin; Parvari, Soraya; MirgaloyBayat, Shahlla; Abbasi, Mehdi (Journal of Contemporary Medical Sciences, 2018)
Objective: Recently growing evident declared that ‘neo-oogenesis’ continues in mature female life span and simultaneously another studies confirmed the presence of spermatogonial stem cells (SSCs). Even though there is agreement between scientist about SSCs population in male gender but on the other side ovarian stem cells have received raising challenges regarding the existence in the surface epithelium of ovary. Mesenchymal stem cells (MSCs) are the most applicable source of stem cells and the common marker of MSCs is Sca-1 so the purpose of this study was to clarify the incidence of stem cells in the surface epithelium of ovary Methods: forty C57BL6 mice were sacrificed and the ovary carefully excised from its surrounding fat tissue, after mechanical and enzymatic digestion cells were stained with Sca1 to estimate the incidence of positive stem cells (SCs) population fluorescence activated cell sorting (FACS). Part of digested cells used for RT-PCR, also histological section prepared for immunohistochemical (IHC) staining of Sca-1 in ovarian surface epithelium (OSE) FACS. Results: The gene expression of Sca-1 was confirmed in the ovarian tissue. As well, localization of Sca-1 positive cells was detected in the germinal layer of ovary and epithelial granular layer of primordial follicles. Moreover, we successfully could isolated the Sca-1positive cells through Conclusion: The present work findings confirmed an inclusive stem cell population in the ovary which can be a strong evident for regeneration of ovarian tissue in either purpose of ovulation scar and neo-oogenesis.